Optimization of Layered Cathode Materials for Lithium-Ion Batteries - Julien, Christian (Materials (Basel), 2016)
This review presents a survey of the literature on recent progress in lithium-ion batteries, with the active sub-micron-sized particles of the positive electrode chosen in the family of lamellar compounds LiMO(2), where M stands for a mixture of Ni, Mn, Co elements, and in the family of yLi(2)MnO(3)•(1 − y)LiNi(½)Mn(½)O(2) layered-layered integrated materials. The structural, physical, and chemical properties of these cathode elements are reported and discussed as a function of all the synthesis parameters, which include the choice of the precursors and of the chelating agent, and as a function of the relative concentrations of the M cations and composition y. Their electrochemical properties are also reported and discussed to determine the optimum compositions in order to obtain the best electrochemical performance while maintaining the structural integrity of the electrode lattice during cycling.